2017
DOI: 10.1159/000480181
|View full text |Cite|
|
Sign up to set email alerts
|

The Protective Effect of Cordycepin On Alcohol-Induced Osteonecrosis of the Femoral Head

Abstract: Background: Alcohol abuse is known to be a leading risk factor for atraumatic osteonecrosis of the femoral head (ONFH), in which the suppression of osteogenesis plays a critical role. Cordycepin benefits bone metabolism; however, there has been no study to determine its effect on osteonecrosis. Methods: Human bone mesenchymal stem cells (hBMSCs) were identified by multi-lineage differentiation. Alkaline phosphatase (ALP) activity, RT-PCR, western blots, immunofluorescent assay and Alizarin red staining of BMSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 45 publications
(46 reference statements)
1
20
0
Order By: Relevance
“…The relative expression of the genes was normalized to b-actin expression. The RT-PCR was carried out as described previously [55]. Primer sequences: PTEN, forward:5 0 -TTT TGA AGA CCA TAA CCC AC-3 0 and reverse 5 0 -TAT CAT TAC ACC AGT TCG TC-3 0 , LncRNA PTENP1, forward:5 0 -TTG TAG TTG TGA TGG AAG TTT GAA T-3 0 and reverse:5 0 -CCA CCC CCA CAA ATA CTC ACA-3 0 , b-actin, forward:5 0 AAG GTG ACA GCA GTC GGT T-3 0 and reverse:5 0 -TGT GTG GAC TTG GGA GAG G-3 0 .…”
Section: Reverse Transcription Polymerase Chain Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative expression of the genes was normalized to b-actin expression. The RT-PCR was carried out as described previously [55]. Primer sequences: PTEN, forward:5 0 -TTT TGA AGA CCA TAA CCC AC-3 0 and reverse 5 0 -TAT CAT TAC ACC AGT TCG TC-3 0 , LncRNA PTENP1, forward:5 0 -TTG TAG TTG TGA TGG AAG TTT GAA T-3 0 and reverse:5 0 -CCA CCC CCA CAA ATA CTC ACA-3 0 , b-actin, forward:5 0 AAG GTG ACA GCA GTC GGT T-3 0 and reverse:5 0 -TGT GTG GAC TTG GGA GAG G-3 0 .…”
Section: Reverse Transcription Polymerase Chain Reactionmentioning
confidence: 99%
“…The sample absorption at 450 nm was analyzed, and a standard curve was generated for each protein. The NE-PER Nuclear and Cytoplasmic Extraction Reagents kit (Pierce Biotechnology, Rockford, IL, USA) was used for nuclear and cytosolic extract preparation as described previously [55].…”
Section: Western Blottingmentioning
confidence: 99%
“…A five-year follow-up study revealed that the combination of implantation of autologous bone marrow cells and auto-iliac cancellous bone grafts generated comparable clinical results with those of head-preserving procedures in medium-sized lesions [16], indicating that BMSCs implantation is promising for ONFH treatment. The findings of a previous investigation demonstrated that the Akt activator and cordycepin promoted BMSC-induced osteogenesis [17, 18]. Furthermore, P-glycoprotein (P-gp) overexpression was found to decrease the risk of steroid-induced ONFH [19].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that in osteoporosis, BMSCs favour adipogenesis over osteogenesis [2][3][4]. Thus, uncovering the complex regulation pathways of normal BMSC differentiation and restoring the decreased osteogenic differentiation of BMSCs is a promising therapeutic strategy for osteoporosis.…”
Section: Introductionmentioning
confidence: 99%